2019
DOI: 10.1186/s12936-019-2915-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection drives IgM and IgG3 subclass bias in Plasmodium falciparum-specific and total immunoglobulin concentration in Western Kenya

Abstract: Background HIV infection is associated with more frequent and severe episodes of malaria and may be the result of altered malaria-specific B cell responses. However, it is poorly understood how HIV and the associated lymphopenia and immune activation affect malaria-specific antibody responses. Methods HIV infected and uninfected adults were recruited from Bondo subcounty hospital in Western Kenya at the time of HIV testing (antiretroviral and co-trimoxazole prophylaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
1
0
0
Order By: Relevance
“…This suggests a synergistic effect on immunoglobulin levels. This finding could be similar to observations made by Odhiambo et al who reported that HIV infection drives IgM and IgG3 subclass bias in Plasmodium falciparum-specific and total immunoglobulin concentration 27 . Both diabetes and HIV drive elevated levels of C-reactive protein as seen from our results, however, IL-6 could be better marker than CRP for the inflammation seen with diabetes and even in HIV co-morbidity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests a synergistic effect on immunoglobulin levels. This finding could be similar to observations made by Odhiambo et al who reported that HIV infection drives IgM and IgG3 subclass bias in Plasmodium falciparum-specific and total immunoglobulin concentration 27 . Both diabetes and HIV drive elevated levels of C-reactive protein as seen from our results, however, IL-6 could be better marker than CRP for the inflammation seen with diabetes and even in HIV co-morbidity.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests a synergistic effect on immunoglobulin levels. This finding could be similar to observations made by Odhiambo et al who reported that HIV infection drives IgM and IgG3 subclass bias in Plasmodium falciparum -specific and total immunoglobulin concentration 27 .…”
Section: Discussionsupporting
confidence: 92%